A connectivity-driven development strategy for Nepal: From a landlocked to a land-linked state - Pradumna B. Rana; Binod Karmacharya (Asian Development Bank Institute (ADBI), 2014)
Nepal's lackluster economic performance during the post-conflict period (that is, after November 2006) has been driven by remittances from the export of labor services and the improved performance of the agricultural sector, which is still very much weather dependent. The authors make the case for a connectivity-driven development strategy for the country. They argue that improved connectivity within Nepal and cross-border connectivity with its neighbors in South Asia, the Association of Southeast Asian Nations (ASEAN), and the People's Republic of China (PRC) that are converting Nepal from a landlocked into a land-linked state, could be important "engines of growth" for the country. It is argued that such a development strategy is not a new one for Nepal as in the past the country was strategically located on the Southwestern Silk Road (SSR). A number of factors have revived the case for making Nepal a land-linked state in Asia. Nepal has adopted a multi-track approach to promoting regional cooperation and integration in connectivity with its neighbors. But a lot more needs to be done, especially in the context of the difficult political situation in the country, and donors have an important role to play in this regard. Ten priority projects to convert Nepal into a land-linked state are identified, but a detailed impact analysis of these projects is beyond the scope of this paper.
Keywords: F15; 330; cross border infrastructure investments; south asia and southeast asia; seamless infrastructure; road and rail land corridor